A comparative study to assess knowledge, health beliefs and preventive practices among women with cervical cancer and general population at tertiary care hospital, New Delhi - Saini, Navreet Kaur; Sharma, Kamlesh Kumari; Mawar, Shashi; Kumar, Lalit; Kumar, Sunesh (International Journal Of Community Medicine And Public Health, 2017)
Background: Awareness regarding cervical cancer, its risk factors and preventive practices is very low among Indian women. The objectives of the study was to compare knowledge, health beliefs and preventive practices regarding cervical cancer among women with cervical cancer and general population at tertiary care hospital, New Delhi; to study the correlation among knowledge, health beliefs and preventive practices of women with cervical cancer and general population and their selected demographic variables. Methods: A comparative study was conducted using descriptive, cross sectional survey among conveniently sampled 100 women with cervical cancer (cases) taking treatment from cancer department of tertiary care hospital and 100 women relatives of patients with non-malignant diseases admitted in different medical, surgical, pediatrics wards of tertiary care hospital (controls). Self-developed, pretested, structured questionnaires validated by experts were used for data collection. Results: Majority of subjects had poor knowledge (78% cases and 90% controls) and positive health beliefs (83% cases and 67% controls). Majority of cases (93%) had fair preventive practices while most of controls (62%) had poor preventive practices regarding cervical cancer. There was positive correlation of knowledge with health beliefs (p=0.0001) and health beliefs with preventive practices (p=0.0469) among controls; but in cases none of these correlations were found. Conclusions: Substantial gaps in knowledge and preventive practices regarding cervical cancer were present in both groups. So there is a need to raise public awareness regarding risk factors and prevention of cervical cancer by modifying the risk factors.